2019
DOI: 10.1093/gerona/glz215
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neural and Muscular Adaptation Processes During Resistance Training by Fish Protein Ingestions in Older Adults

Abstract: Assessments of both neural and muscular adaptations during interventions would provide valuable information for developing countermeasures to age-related muscle dysfunctions. We investigated the effect of fish protein ingestion on training-induced neural and muscular adaptations in older adults. Twenty older adults participated 8 weeks of isometric knee extension training intervention. The participants were divided into two groups who took fish protein (n = 10, Alaska pollack protein, APP) or casein (n = 10, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 38 publications
2
28
3
Order By: Relevance
“…Since we noted no significant increases in muscle volume-related variables, the muscle strength gain in the present study may be primarily due to neural adaptations. In our previous study, increases in muscle volume following resistance training were observed in older adults with APP ingestion, but not in older adults with CAS ingestion (9). These present and previous findings suggest that the same training regimen with APP and CAS ingestion induces strength gains and muscular adaptations that differ in young and older adults.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Since we noted no significant increases in muscle volume-related variables, the muscle strength gain in the present study may be primarily due to neural adaptations. In our previous study, increases in muscle volume following resistance training were observed in older adults with APP ingestion, but not in older adults with CAS ingestion (9). These present and previous findings suggest that the same training regimen with APP and CAS ingestion induces strength gains and muscular adaptations that differ in young and older adults.…”
Section: Discussionsupporting
confidence: 58%
“…Although we investigated the effect of APP ingestion on muscle strength, muscle volume, and motor unit activations in the present and previous study (9,22), detailed physiological mechanisms/pathways for the effect of fish protein ingestion on neuromuscular systems have not been clarified. Recently, the effects of fish-derived omega-3 fatty acids on muscle strength and volume has seen considerable interest (45, 46).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations